2020
DOI: 10.1038/s41422-019-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian ALKBH1 serves as an N6-mA demethylase of unpairing DNA

Abstract: N 6-methyladenine (N 6-mA) of DNA is an emerging epigenetic mark in mammalian genome. Levels of N 6-mA undergo drastic fluctuation during early embryogenesis, indicative of active regulation. Here we show that the 2-oxoglutarate-dependent oxygenase ALKBH1 functions as a nuclear eraser of N 6-mA in unpairing regions (e.g., SIDD, Stress-Induced DNA Double Helix Destabilization regions) of mammalian genomes. Enzymatic profiling studies revealed that ALKBH1 prefers bubbled or bulged DNAs as substrate, instead of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 70 publications
(128 reference statements)
4
77
0
Order By: Relevance
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs. For example, R-loop, a form of unpaired DNAs, is a known ALKBH1 substrate that only accounts for about 5% of the human genome (Sanz et al, 2016;Zhang et al, 2020a).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Despite that ALKBH1 has recently been reported as a 6mA demethylase (Xiao et al, 2018;Xie et al, 2018), which is by far the only one identified in human, we did not observe discernible difference in the 6mA levels in hESCs, hMSCs or hVSMCs caused by ALKBH1 deficiency, consistent with the recent report that ALKBH1 fails to eliminate 6mA in mESCs or HEK293T cells (Liu et al, 2020). Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs. For example, R-loop, a form of unpaired DNAs, is a known ALKBH1 substrate that only accounts for about 5% of the human genome (Sanz et al, 2016;Zhang et al, 2020a).…”
supporting
confidence: 85%
“…Given that two studies have shown that ALKBH1 preferably demethylates 6mA on unpaired DNAs (Tian et al, 2020;Zhang et al, 2020a), our results imply that there might be few unpaired DNAs in the normally cultured hESCs, hMSCs and hVSMCs. For example, R-loop, a form of unpaired DNAs, is a known ALKBH1 substrate that only accounts for about 5% of the human genome (Sanz et al, 2016;Zhang et al, 2020a). Accordingly, the potential alteration in 6mA levels on R-loop may be undetectable in our study.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Here we characterized, for the first time, the in vitro binding activity of the YTH domain of human YTHDC1 as preferentially targeting DNA, relative to RNA. YTH binds N6mA in the context of ssDNA, an activity comparable to that found in the human enzymatic activities of the MettL3–14 MTase complex and the demethylase Alkbh1, as they each act on damaged or unpaired DNA ( 26 , 37 ). Additional study will be required to address whether YTHDC1 is involved in the recognition of DNA adenine methylation in vivo and, if so, its impact on chromatin organization.…”
Section: Discussionmentioning
confidence: 53%
“…Human and mouse homologs (Alkbh1 and Alkbh4) of the E. coli repair enzyme AlkB can function as sequence-independent DNA N6mA demethylases ( 9 , 10 , 13 ), and at least the mouse Alkbh1 prefers locally-unpaired DNA substrates ( 37 ). It is intriguing that both the writer (MTase) and eraser (demethylase) of the N6mA methyl mark act on single-stranded and transiently unpaired DNA.…”
Section: Introductionmentioning
confidence: 99%